High prevalence of echocardiographic abnormalities in older HIV-infected children taking antiretroviral therapy. (28th November 2018) - Majonga, Edith D.; Rehman, Andrea M.; Simms, Victoria; Mchugh, Grace; Mujuru, Hilda A.; Nathoo, Kusum; Odland, Jon O.; Patel, Mohammad S.; Kaski, Juan P.; Ferrand, Rashida A.
Abstract : Background: Antiretroviral therapy (ART) has decreased mortality so that increasing numbers of children with HIV are reaching adolescence. However, longstanding HIV infection and/or its treatment in children is associated with noninfectious complications including cardiac disease. We investigated the prevalence, spectrum and risk factors for echocardiographic abnormalities among children established on ART. Methods: HIV-infected children aged 6–16 years, on ART at least 6 months were enrolled into a cross-sectional study from a public-sector paediatric HIV clinic in Harare, Zimbabwe. A standardized examination including transthoracic echocardiography was performed. Local echocardiographic reference ranges were used to define cardiac abnormalities. Logistic regression was used to examine the association between cardiac abnormalities and risk factors. Results: Of the 201participants recruited, 92 (46%) were girls and median age was 11 (IQR 9–12) years; CD4 + cell count was 727 cells/μl (IQR 473–935) and 154 (78%) had viral load less than 400 copies/ml. Echocardiographic abnormalities were found in 83 (42%); left ventricular (LV) diastolic dysfunction was the most common abnormality 45 (23%) and LV hypertrophy in 22 (11%). LV and left atrial dilatation were found in 9 (5%) and 16 (8%), respectively. Right ventricular dilatation and systolic dysfunction were found in 13 (7%) and 4 (2%), respectively, of whom 60% had concurrent left heart abnormalities. Current use of nevirapine was associated with LVH [aOR 3.14 (1.13–8.72; P = 0.03)] and hypertension was associated with LV diastolic dysfunction [aOR 3.12 (1.48–6.57; P < 0.01)]. Conclusion: HIV-infected children established on ART have a high burden of echocardiographic abnormalities. Right heart disease was predominantly associated with left heart abnormalities and may be part of a global cardiomyopathic process. Further studies are needed to investigate the natural history, aetiology, and pathogenesis of these abnormalities, so that appropriate monitoring and treatment strategies can be developed. Abstract : Supplemental Digital Content is available in the text